Decratonization by rifting enables orogenic reworking and transcurrent dispersal of old terranes in NE Brazil - Carlos E. Ganade (Nature Portfolio, 2021)
Abstract Dispersion and deformation of cratonic fragments within orogens require weakening of the craton margins in a process of decratonization. The orogenic Borborema Province, in NE Brazil, is one of several Brasiliano/Pan-African late Neoproterozoic orogens that led to the amalgamation of Gondwana. A common feature of these orogens is that a period of extension and opening of narrow oceans preceded inversion and collision. For the case of the Borborema Province, the São Francisco Craton was pulled away from its other half, the Benino-Nigerian Shield, during an intermittent extension event between 1.0–0.92 and 0.9–0.82 Ga. This was followed by inversion of an embryonic and confined oceanic basin at ca. 0.60 Ga and transpressional orogeny from ca. 0.59 Ga onwards. Here we investigate the boundary region between the north São Francisco Craton and the Borborema Province and demonstrate how cratonic blocks became physically involved in the orogeny. We combine these results with a wide compilation of U–Pb and Nd-isotopic model ages to show that the Borborema Province consists of up to 65% of strongly sheared ancient rocks affiliated with the São Francisco/Benino-Nigerian Craton, separated by major transcurrent shear zones, with only ≈ 15% addition of juvenile material during the Neoproterozoic orogeny. This evolution is repeated across a number of Brasiliano/Pan-African orogens, with significant local variations, and indicate that extension weakened cratonic regions in a process of decratonization that prepared them for involvement in the orogenies, that led to the amalgamation of Gondwana.